From the nest to the world: helicopter parenting and challenges in young adult social integration - Yilmaz, Yelda; Artan, Taner; Gurbanova, Farida; Aliyeva, Nargiz (Frontiers in Psychology, 2025)
IntroductionHelicopter parenting is a new parenting style that has become widespread globally. This study aimed to evaluate the effects of helicopter parenting experiences on Turkish young adults, focusing on self-determination and fear of intimacy.MethodsA cross-sectional design was used with 800 Turkish young adults. Data were collected using the Personal Information Form, Perceived Helicopter Parenting Attitude Scale, Self-Determination Scale, and Fear of Intimacy Scale.ResultsResults showed a significant negative correlation between perceived helicopter parenting and self-determination. There was also a significant positive correlation between perceived helicopter parenting and fear of intimacy. Furthermore, self-determination mediated the relationship between both maternal and paternal helicopter parenting attitudes and fear of intimacy.DiscussionThe findings suggest the importance of increasing awareness about helicopter parenting and its impact on young adults' future lives.